Metabolic Syndrome: An Emerging Threat - Rahman, Quazi Audry Arafat; Razzak, Md Abdur; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Metabolic syndrome (MetS) is a multifaceted syndrome, which occurs frequently in the general population. It represents a cluster of metabolic abnormalities that include hypertension, central obesity, insulin resistance, and atherogenic dyslipidemia, and is strongly associated with an increased risk for developing diabetes and atherosclerotic and nonatherosclerotic cardiovascular disease (CVD). The pathogenesis of MetS involves both genetic and acquired factors that contribute to the final pathway of inflammation that leads to CVD. MetS has gained significant importance recently due to the exponential increase in obesity worldwide. Early diagnosis is important in order to employ lifestyle and risk factor modification. Here, we review the epidemiology, diagnostic criteria, pathogenesis and disease associations of MetS, and summarize existing management modalities. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 203-208